THE DIFFERENCES OF RELIGIOSITY AND ACHIEVEMENT MOTIVATION AMONG STUDENTS OF STATE ISLAMIC UNIVERSITY OF MAULANA MALIK IBRAHIM MALANG - Susilawati, Samsul (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Religiosity is a religious understanding and appreciation, and depth of faith expressed by daily worship, praying, and reading of scripture. Religiosity could give positive roles for student motivation. The Correct understanding of religion and the practices of religious beliefs will distinguish someone from others. With a correct understanding and practice of religious beliefs, it will form skilled, responsible, honest, discipline, loyal, optimistic, and tolerant individuals. By understanding of the faith and the religion, students have a high achievement motivation to complete their daily task and finish their study on time. The higher the person's religious level the easier it will be for them to better complete their tasks, duties and responsibilities and to strive for difficulties in the face of religious values.